Effects of Kahoot!-mediated vocabulary instruction on vocabulary gains and learner attitudes: A mixed-methods study in a Vietnamese public high school - Huyen Dang Huynh; Nghi Tran Tin (English Language Teaching Educational Journal, 2026)
This study examined the hypothesis of whether Kahoot!-mediated instruction could enhance the learning of English vocabulary in Grade 11 students and whether students had a positive perception of the platform in a Vietnamese high school setting. The research addressed a practical issue that has been used in numerous EFL classrooms in Lam Dong Province: the students were expected to achieve the curriculum and proficiency requirements, and yet, many remained unable to remember and apply vocabulary correctly in class and test results. The mixed-methods design was used during eight weeks and included 62 students (11th grade) in an experimental group (n = 27) and a control group (n = 35). Vocabulary pre-tests and post-tests, and a Likert-scale attitude questionnaire were used to gather quantitative data, and semi-structured interviews with the chosen students of the experimental group were used to collect qualitative data. Experimental group was vocabulary training using Kahoot! and the control group used standard vocabulary training. The results revealed that a definite improvement was observed in the experimental group between pre-test and post-test compared to the control group where a definite change in the weak and average bands could be seen to fairly good and good bands. The attitude outcomes were also good: students evaluated Kahoot! to be fun and helpful in practice and as effective in learning new words. The data of interviews also indicated that Kahoot! encouraged paying attention, playing, competition, fun, and the practice of vocabulary. The paper claims that Kahoot! is not just a motivational tool; when it is incorporated into the systematic lessons of the curriculum, it can be used to facilitate the process of vocabulary learning and to provide the environment of a more interactive learning experience. The article provides context-related data of a Vietnamese secondary-school context and explains how gamified platforms could be organized towards pedagogical objectives, instead of being used as a form of entertainment.